Sun, Sex, and Gold: Tourism and Sex Work in the Caribbean - Kempadoo, Kamala (Rowman & Littlefield Publishers, 1999)
With tourism accounting for approximately thirty percent of the Caribbean's GDP and twenty-four percent of employment, a link between the sex trade and the tourism industry has gained recent attention. Shifts in global production, an increase of disposable income for pleasure and recreation, and a desire by North Americans and Europeans for an experience of 'exotic' cultures, are often claimed to be the cause. This volume explores the connections between the global economy and sex work, focusing on the experiences and views of women, men, and children who sell sex. Apart from attention to sex tourism in Cuba, the Dominican Republic, Barbados, and Jamaica, the book also examines sex work in the gold mining industry in the hinterlands of Suriname and Guyana, and in the entertainment sector in Belize and the Dutch Antilles. It presents new insights into the Caribbean sex trade and provides proposals and strategies for addressing the situation in the twenty-first century.